(untitled) (Research, Society and Development, 2021)
In the dental area of maxillofacial surgery, a large number of cases of unerupted and impacted teeth is commonly found in patients seen at the Araçatuba Dental School - UNESP. The aim of this study was to determine the profile of patients and third molars indicated for extraction, as well as their surgical treatment. For the research, the profile of patients and teeth extracted from treatments carried out in the college’s clinics were obtained, where a form was applied to each extracted tooth. The personal data of the patients were obtained from the files, the presence or not of systemic disease, Pell & Gregory and Winter classification for third molars, if the tooth is causing any mechanical, nervous, infectious or tumoral disorder. There is also filling in the form for the postoperative period whether or not there was any type of disorder. Over three years, 134 patients were seen, 57% female and 43% male, with the greatest demand for care being in the age group of 20 to 29 years, totaling 275 extracted teeth. In 54% of the cases, mandibular molars were extracted, with position A and class II being more prevalent according to Pell & Gregory’s classification. For all extracted third molars, the most frequent position was the vertical with 58% of cases according to the Winter classification. It is concluded that most patients are young females, with lower third molar extraction procedures prevailing. Moreover, the most frequent postoperative complications were edema, alveolitis and inferior alveolar nerve paresthesia.